NAZHIR'S ABILITY TO REALIZE PRODUCTIVE WAQF IN ACEH CITY - Abdul Jalil, Husni; Munir, Badrul; Wahyudi, Setia (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
One of the important requirements that a waqf nazhir must have according to the provisions of waqf jurisprudence and Law Number 41 of 2004 concerning waqf is the ability to manage and develop waqf assets so that they become productive waqf. However, preliminary data shows that the number of productive waqfs in the city of Banda Aceh is very small compared to unproductive waqfs. The formulation of the problem in this research is how nazhir's ability to create productive waqf in the city of Banda Aceh. The method used in this research is a qualitative method which is a field or empirical study and the focus of the study is the nazhir's ability to create productive waqf in the city of Banda Aceh. The results of the research show that the ability of nazhir to create productive waqf in the city of Banda Aceh is still low, this can be seen from the fact that not all nazhir have carried out planning, implementation, evaluation and solutions in realizing productive waqf. Nazir, who has carried out planning, evaluation and solutions, does not yet have special instruments related to these activities, so the number of waqf assets managed productively is still small, 31 plots out of a total of 787 plots.